The Role of Beauty Content Creators and TikTok Affiliates in Influencing Local Skincare Product Purchase Decisions - Simangunsong, Sixson Roberto; Amanda, Nayla; Simanjuntak, Josuwandi (PT FORMOSA CENDEKIA GLOBAL, 2025)
The development of digital technology has significantly changed marketing strategies, including in the beauty industry. One of the modern forms of marketing that is now very popular is through social media platforms such as TikTok. Many beauty content creators are actively sharing reviews, tutorials, and recommendations for local skincare products. Not only that, TikTok's affiliate program also makes it easier for content creators to market products directly to their audience. This phenomenon encourages changes in consumer behavior, especially in making decisions to purchase local skincare products. This study uses a quantitative approach with a survey method. Data will be collected through the distribution of questionnaires to respondents who are active users of TikTok and have purchased local skincare products that are recommended to beauty creators. The independent variable in this study is the role of beauty content creators and TikTok affiliates, while the dependent variable is the purchase decision. The data analysis technique used is multiple linear regression analysis to see the effect simultaneously and partially. From this study, it is hoped that beauty content creators and TikTok affiliates have a significant influence on local skincare product purchase decisions. Trust in content creators, the quality of the content presented, and the ease of access to purchases through affiliate links are expected to be the main factors in encouraging consumers to buy promoted products.